Exploring the role of high government debt on economic growth: A nonlinearity and threshold analysis for Africa's developing countries - Nokwanda Mqolombeni; Devi D. Tewari; Kehinde Damilola Ilesanmi (Economies, 2023)
Purpose: This paper empirically investigated the impact of high government debt on economic growth, using a panel data of 12 developing countries in Africa for the period between 1991 and 2020. Furthermore, it sought to find the existence of nonlinearity between government debt and economic growth. The study used a cross-country panel data approach estimated through the panel smooth transition regression to find the threshold effect. The results reveal a threshold of 60.5% of government debt on economic growth, suggesting an inverted U-shaped relationship between government debt and economic growth for the whole sample. After this threshold, additional government debt starts impeding economic growth. The estimated slope parameter of 18.11 supports the smoothness of government debt from a low regime to a high regime of debt. In the lower debt regime, government debt boosts economic growth; however as the level of debt growth surpasses the peak point, economic growth decreases. By implication, policymakers should have strict debt management policies in place to keep the level of government debt low, and be able to respond robustly to an economic shock. While resorting to borrowing to finance public spending, especially during economic crises, may be an imperative, it should be done in a circumspect manner so that the borrowings are kept at tolerable levels and reduced and/or repaid when there is a recovery in the economy.
Keywords: 330; economic growth; Africa; developing countries; government debt; PSTR model